Income inequality and welfare spending: A disaggregated analysis - Karl Ove Moene; Michael Wallerstein (University of Oslo, Department of Economics, 2003)
The welfare state is generally viewed as either providing redistribution from rich to poor or as providing publicly-financed insurance. Both views are incomplete. Welfare policies provide both insurance and redistribution in varying amounts, depending on the design of the policy. We explore the political consequences of the mix of redistribution and insurance in the context of studying the impact of income inequality on expenditures in different categories of welfare spending in advanced industrial socieities from 1980-1995. We find that spending on pensions, health care, family benefits, poverty alleviation and housing subsidies is largely uncorrelated with income inequality, but that spending on income replacement programs such as unemployment insurance, sickness pay, occupational illness and disability are signinficantly higher in countries with more egalitarian income distributions. We show that this pattern is exactly what a theory of political support for redistributive social insurance programs would predict.
Keywords: D62; H23; H53; J65; 330; Welfare state; insurance; redistribution; income inequality; Einkommensverteilung; Einkommensumverteilung; Sozialstaat; Öffentliche Sozialausgaben; Sozialtransfer; Industriestaaten